Occult Neoplasm (Mucoepidermoid carcinoma) in a Parotid Cyst: A Case Study - Anuja Santosh Kulkarni; Prabodh Karnik (Medicine and Medical Research: New Perspectives Vol. 12, 2024)
Mucoepidermoid carcinoma (MEC) is the most common malignant salivary gland tumor accounting for 10–15% of all salivary gland neoplasms and 30% of all salivary malignancies followed by adenoid cystic carcinoma (ACC). A parotid cyst is a well-documented clinical entity. Here we report a case of low-grade mucoepidermoid carcinoma as an occult neoplasm; a rare presentation of a parotid cyst in a 35-year-old female patient who presented with a well-defined small cystic swelling of the right parotid gland; cytologically consistent with a simple parotid gland cyst. The purpose of this article is to create awareness about the existence of an occult neoplasm (low-grade mucoepidermoid carcinoma in this case) in a small simple parotid cyst in a young female an unusual presentation and management of parotid cyst. In the present case report, mucoepidermoid carcinoma caused a significant obstruction of the parotid duct thereby giving rise to a simple retention cyst of the parotid. Treatment of a simple parotid cyst should be facial nerve-preserving superficial parotidectomy with meticulous, histology and careful follow-up.